An investigation into reducing the spindle acceleration energy consumption of machine tools. (1st February 2017) - Lv, Jingxiang; Tang, Renzhong; Tang, Wangchujun; Liu, Ying; Zhang, Yingfeng; Jia, Shun
Abstract: Machine tools are widely used in the manufacturing industry, and consume large amount of energy. Spindle acceleration appears frequently while machine tools are working. It produces power peak which is highly energy intensive. As a result, a considerable amount of energy is consumed by this acceleration during the use phase of machine tools. However, there is still a lack of understanding of the energy consumption of spindle acceleration. Therefore, this research aims to model the spindle acceleration energy consumption of computer numerical control (CNC) lathes, and to investigate potential approaches to reduce this part of consumption. The proposed model is based on the principle of spindle motor control and includes the calculation of moment of inertia for spindle drive system. Experiments are carried out based on a CNC lathe to validate the proposed model. The approaches for reducing the spindle acceleration energy consumption were developed. On the machine level, the approaches include avoiding unnecessary stopping and restarting of the spindle, shortening the acceleration time, lightweight design, proper use and maintenance of the spindle. On the system level, a machine tool selection criterion is developed for energy saving. Results show that the energy can be reduced by 10.6% to more than 50% using these approaches, most of which are practical and easy to implement. Highlights: Energy consumption of spindle acceleration (ESA) of machine tools has been modeled. The ESA can be predicted by design parameters of machine tools without experiments. ESA can be saved on both machine level and system level. Shortening acceleration time and lightweight design reduce the ESA. Proper use of the spindle and machine tool selection can help to reduce the ESA.